CREATIVE APPROACHES TO COMPUTER SCIENCE EDUCATION - Raspopov, V.B.; Manzhula, A.M. (Journal of Information Technologies in Education (ITE), 2010)
Using the example of PPS «Toolbox of multimedia lessons «For Children About Chopin» we demonstrate the possibility of involving creative students in developing the software packages for educational purposes. Similar projects can be assigned to school and college students studying computer sciences and informatics, and implemented under the teachers’ supervision, as advanced assignments or thesis projects as a part of a high school course IT or Computer Sciences, a college course of Applied Scientific Research, or as a part of preparation for students’ participation in the Computer Science competitions or IT- competitions of Youth Academy of Sciences ( MAN in Russian or in Ukrainian).